Effect of the addition mechanism of ZnO sintering aid on densification, microstructure and electrical properties of Ba(Zr, Y)O3-δ proton-conducting perovskite. (29th July 2021) - Soares, Helena Sofia; Antunes, Isabel; Loureiro, Francisco J.A.; Pérez-Coll, Domingo; Willinger, Marc-Georg; Brandão, Ana D.; Mather, Glenn C.; Fagg, Duncan P.
Abstract: We explore three different potential mechanisms to introduce 4 mol% ZnO sintering additive to the promising yttrium-doped barium zirconate (Ba(Zr, Y)O3-δ, BZY) proton conductor. The mechanisms involve Zn substitution for Y, Zr, or B-site cation excess. The addition of ZnO promotes high densification levels (up to 98% of the theoretical value) at 1300 °C, irrespective of the mechanism. However, scanning electron microscopy shows that the B-site cation excess mechanism leads to an impaired grain growth compared to the other mechanisms. Rietveld refinement of the lattice-parameters and scanning transmission electron microscopy-energy dispersive X-ray spectroscopy indicates that Zn resides in both grains and grain boundaries in all cases. Determination of partial conductivities demonstrates that the Zr substitution mechanism provides slightly higher values of bulk protonic conductivity, as well as a higher hydration enthalpy. In contrast, the B-site excess mechanism provides the highest specific grain-boundary conductivity, as a result of greater Zn segregation to the grain boundary. Highlights: Three different mechanisms to introduce ZnO sintering additive to BZY are explored. The bulk protonic conductivity is slightly enhanced by the Zr substitution. The specific grain boundary conductivity is enhanced by a B-site cation excess.